tìm x biết x(x-4)+2(x-4)=0
tìm x , biết :
a, ( x mũ 3 - 4 x mũ 2 ) - ( x -4 ) = 0
b, x mũ 5 - 9x = 0
c, ( x mxu 3 - x mũ 2 ) mũ 2 - 4 x mũ 2 + 8x - 4 = 0
a/
\(x^3-4x^2-\left(x-4\right)=0\)
\(\Leftrightarrow x^2\left(x-4\right)-\left(x-4\right)=0\)
\(\Leftrightarrow\left(x-4\right)\left(x^2-1\right)=0\)
\(\Leftrightarrow\left(x-4\right)\left(x-1\right)\left(x+1\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x-4=0\\x-1=0\\x+1=0\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}x=4\\x=1\\x=-1\end{matrix}\right.\)
b/
\(x^5-9x=0\)
\(\Leftrightarrow x\left(x^4-9\right)=x\left(x^2-3\right)\left(x^2+3\right)=0\)
\(\Leftrightarrow x\left(x-\sqrt{3}\right)\left(x+\sqrt{3}\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=0\\x=\sqrt{3}\\x=-\sqrt{3}\end{matrix}\right.\)
c/
\(\left(x^3-x^2\right)^2-4x^2+8x-4=0\)
\(\Leftrightarrow x^4\left(x-1\right)^2-4\left(x-1\right)^2=0\)
\(\Leftrightarrow\left(x-1\right)^2\left(x^4-4\right)=0\)
\(\Leftrightarrow\left(x-1\right)^2\left(x^2-2\right)\left(x^2+2\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x-1=0\\x^2-2=0\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}x=1\\x=\pm\sqrt{2}\end{matrix}\right.\)
tìm x biết x^2 (x^2+ 4 ) - x^2 -4 = 0
\(\Leftrightarrow x^2\left(x^2+4\right)-\left(x^2+4\right)=0\)
\(\Leftrightarrow\left(x^2+4\right)\left(x^2-1\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x^2-1=0\\x^2+4=0\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}x^2=1\\x^2=-4\left(vn\right)\end{matrix}\right.\)
\(\Leftrightarrow x=\pm1\)
Tìm x biết a) x(x-25)=0 b)2x(x-4)-x(2x-1)=-28 c)x^2 -5x=0 d)(x-2)^2-(x+1)(x+3)=-7 e)(3x+5).(4-3x)=0 f)x^2-1/4=0
a: \(x\in\left\{0;25\right\}\)
c: \(x\in\left\{0;5\right\}\)
5A. Tìm x, biết:
a) 8x(x - 2017) - 2x + 4034 = 0; b)
x + x2
2 8
= 0;
c) 4 - x = 2( x -4)2; d) (x2 + 1)(x - 2) + 2x = 4.
5B. Tìm x, biết:
a) x4 -16x2 =0; c) x8 + 36x4 =0;
b) (x - 5)3 - x + 5 = 0; d) 5(x - 2 ) - x2 + 4 = 0.
a: \(8x\left(x-2017\right)-2x+4034=0\)
\(\Leftrightarrow\left(x-2017\right)\left(8x-2\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=2017\\x=\dfrac{1}{4}\end{matrix}\right.\)
Tìm x biết (x^2-2)^2+4(x-1)^2-4(x^2-2)(x-1)=0
$(x^2-2)^2+4(x-1)^2-4(x^2-2)(x-1)=0$
$\Leftrightarrow(x^2-2)^2-4(x^2-2)(x-1)+4(x-1)^2=0$
$\Leftrightarrow(x^2-2)^2-2\cdot(x^2-2)\cdot2(x-1)+[2(x-1)]^2=0$
$\Leftrightarrow[(x^2-2)-2(x-1)]^2=0$
$\Leftrightarrow(x^2-2-2x+2)^2=0$
$\Leftrightarrow(x^2-2x)^2=0$
$\Leftrightarrow x^2-2x=0$
$\Leftrightarrow x(x-2)=0$
\(\Leftrightarrow\left[{}\begin{matrix}x=0\\x-2=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=0\\x=2\end{matrix}\right.\)
Vậy: $x\in\{0;2\}$.
tìm x biết :
4x(x+1) = 8(x+1)
x(2x+1) +\(\dfrac{1}{3}-\dfrac{2}{3}x=0\)
x(x-4) +(x-4)2 =0
3) \(x\left(x-4\right)+\left(x-4\right)^2=0\Leftrightarrow\left(x-4\right)\left(x+x-4\right)=0\Leftrightarrow2\left(x-4\right)\left(x-2\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x-4=0\\x-2=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=4\\x=2\end{matrix}\right.\)
4x.(x+1)-8(x+1)=0
(4x-8)(x+1)=0
suy ra x=2 hoặc x=-1
1) \(4x\left(x+1\right)=8\left(x+1\right)\Leftrightarrow4x^2+4x=8x+8\Leftrightarrow4x^2-4x-8=0\Leftrightarrow x^2-x-2=0\Leftrightarrow\left(x-2\right)\left(x+1\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=2\\x=-1\end{matrix}\right.\)
Tìm x, biết:
a) 8x(x - 2017) - 2x + 4034 = 0; b) x 2 + x 2 8 = 0;
c) 4 - x = 2 ( x - 4 ) 2 ; d) ( x 2 + 1)(x - 2) + 2x = 4.
Tìm x biết
( x+1 ).( x-2 ) >0 ;
( x-2 ).( x-3 ) >0 ;
x ( x-4 ) >0 ;
x ( x-4 ) <0
Bài 1 : tìm x biết
a) ( /x/ - 1/4 ) . ( x2 - 9 ) = 0
b) ( /x/ + 2 ) . ( /x/ - 4 ) = 0
c) ( x2 - 1/4 ) . ( x2 - 1/10 ) = 0
d) ( x + 2 ) . ( x - 3 ) < 0
e) ( x - 1/4 ) . ( x + 1/2 ) > 0
d) (x + 2)(x - 3) < 0
Ta có bảng :
x -2 3 |
x + 2 - 0 + + |
x - 3 - - 0 + |
(x + 2)(x - 3) + - + |
Vậy (x + 2)(x - 3) < 0
Khi : \(\hept{\begin{cases}x+2>0\\x-3< 0\end{cases}\Leftrightarrow\hept{\begin{cases}x>-2\\x< 3\end{cases}\Leftrightarrow}-2< x< 3}\)